Analysis of Planned Flood Discharge Using HEC-HMS Software on the Keser River, Trenggalek Regency - Teddy Satria Kartadipura; Minarni Nur Trilita (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
To mitigate seasonal flooding in the Keser River watershed, Trenggalek Regency, East Java, this study estimated design rainfall and flood discharges using the HEC-HMS hydrological model based on rainfall records from 2014–2024. Areal rainfall was calculated using the Thiessen Polygon method, while frequency analysis identified the Log Pearson Type III distribution as the most appropriate probability model according to the Chi-Square and Kolmogorov–Smirnov goodness-of-fit tests. The 43.06 km² watershed was delineated into seven sub-watersheds using DEM and land-use data. Rainfall losses and runoff transformation were simulated using the SCS Curve Number (SCS-CN) and SCS Unit Hydrograph methods, respectively. The simulated peak discharges at the watershed outlet were 512.9, 678.5, 772.3, 877.8, 947.9, and 1,011.7 m³/s for the 2-, 5-, 10-, 25-, 50-, and 100-year return periods, respectively. The simulated hydrographs exhibited a steep rising limb followed by a gradual recession limb, indicating rapid runoff generation and delayed flow attenuation. These results demonstrate that the HEC-HMS model effectively represents the hydrological behavior of the Keser River watershed and provides reliable design flood estimates to support flood mitigation planning and sustainable water resources management. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land